2016
DOI: 10.1186/s12913-016-1361-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of major cardiovascular events in patients with diabetes using primary care data

Abstract: BackgroundRoutine primary care data are increasingly being used for evaluation and research purposes but there are concerns about the completeness and accuracy of diagnoses and events captured in such databases. We evaluated how well patients with major cardiovascular disease (CVD) can be identified using primary care morbidity data and drug prescriptions.MethodsThe study was conducted using data from 17,230 diabetes patients of the GIANTT database and Dutch Hospital Data register. To estimate the accuracy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…For depression in males, our data (15.8) is higher than other European countries (4.4–12.7). Compared to other European research studies, our findings are comparable to Sweden for anxiety, higher for depression but lower for dementia (5.6% cognitive disorders compared to 16% dementia in Sweden) [ 10 ], and higher for depression compared to Wales (17.1 compared to 9.3) [ 22 ] The rate of diagnosed depression is considerably higher in our study population (17.1%) than that reported in Ireland’s National Longitudinal Study on Ageing (5%) [ 6 ]. Previous attempts to estimate the prevalence of alcohol misuse in older people have proven difficult for a variety of reasons, including a tendency on the part of study respondents to under-report usage [ 23 ].…”
Section: Discussionsupporting
confidence: 70%
“…For depression in males, our data (15.8) is higher than other European countries (4.4–12.7). Compared to other European research studies, our findings are comparable to Sweden for anxiety, higher for depression but lower for dementia (5.6% cognitive disorders compared to 16% dementia in Sweden) [ 10 ], and higher for depression compared to Wales (17.1 compared to 9.3) [ 22 ] The rate of diagnosed depression is considerably higher in our study population (17.1%) than that reported in Ireland’s National Longitudinal Study on Ageing (5%) [ 6 ]. Previous attempts to estimate the prevalence of alcohol misuse in older people have proven difficult for a variety of reasons, including a tendency on the part of study respondents to under-report usage [ 23 ].…”
Section: Discussionsupporting
confidence: 70%
“…The proxy used in our study showed a sensitivity of 85% and a specificity of 75% in identifying patients with a history of major CVD. [18] Although this is rather low from a diagnostic perspective, the use of drug proxies is still useful to identify patients who may be less adherent to their medication. A small number of patients (0.9%) switched to other antihypertensive drug classes that were not included in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Type of prevention was defined as primary or secondary based on the prescription of a proxy indicating a previous cardiovascular event. [18] Patients who were dispensed at least two prescriptions of a platelet aggregation inhibitor, organic nitrate and/or a vitamin K antagonist in the year before the index date were categorized as secondary prevention patients. All others were considered primary prevention patients.…”
Section: Methodsmentioning
confidence: 99%
“…Stratified (to take into account matching) Cox proportional hazard regression was used to evaluate the risk of receiving antibiotic treatment during periods that statins are used compared with non‐use periods. The following variables were considered as potential (proxies for) risk factors for receiving antibiotic treatment: cardiovascular drugs, antithrombotic agents, systemic corticosteroids, immunosuppressants, antivirals, antineoplastics, and drugs for obstructive airway diseases, acid‐suppresive drugs, number of antibiotic prescriptions in the previous year, and duration of diabetes. All potential risk factors were included in the final multivariate model.…”
Section: Methodsmentioning
confidence: 99%